Experience of implementing a National pre-hospital Code Red bleeding protocol in Scotland. Issue 1 (January 2017) - Reed, Matthew J.; Glover, Alison; Byrne, Lauren; Donald, Michael; McMahon, Niall; Hughes, Neil; Littlewood, Nicola K.; Garrett, Justin; Innes, Catherine; McGarvey, Margaret; Hazra, Eleanor; Rawlinson, P. Sam M.; et al.
Abstract: Introduction: The Scottish Transfusion and Laboratory Support in Trauma Group (TLSTG) have introduced a unified National pre-hospital Code Red protocol. This paper reports the results of a study aiming to establish whether current pre-hospital Code Red activation criteria for trauma patients successfully predict need for in hospital transfusion or haemorrhagic death, the current admission coagulation profile and Concentrated Red Cell (CRC): Fresh Frozen Plasma (FFP) ratio being used, and whether use of the protocol leads to increased blood component discards? Methods: Prospective cohort study. Clinical and transfusion leads for each of Scotland's pre-hospital services and their receiving hospitals agreed to enter data into the study for all trauma patients for whom a pre-hospital Code Red was activated. Outcome data collected included survival 24 h after Code Red activation, survival to hospital discharge, death in the Emergency Department and death in hospital. Results: Between June 1 st 2013 and October 31 st 2015 there were 53 pre-hospital Code Red activations. Median Injury Severity Score (ISS) was 24 (IQR 14–37) and mortality 38%. 16 patients received pre-hospital blood. The pre-hospital Code Red protocol was sensitive for predicting transfusion or haemorrhagic death (89%). Sensitivity, specificity, positive and negative predictive values of the pre-hospital SBP <90 mmHg component were 63%, 33%, 86% and 12%. 19% had an admission prothrombin time >14 s and 27% had a fibrinogen <1.5 g/L. CRC: FFP ratios did not drop to below 2:1 until 150 min after arrival in the ED. 16 red cell units, 33 FFP and 6 platelets were discarded. This was not significantly increased compared to historical data. Conclusions: A National pre-hospital Code Red protocol is sensitive for predicting transfusion requirement in bleeding trauma patients and does not lead to increased blood component discards. A significant number of patients are coagulopathic and there is a need to improve CRC: FFP ratios and time to transfusion support especially FFP provision. Training clinicians to activate pre-hospital Code Red earlier during the pre-hospital phase may give blood bank more time to thaw and prepare FFP and may improve FFP administration times and ratios so long as components are used upon their availability.